The Influence of Man on Marine Life - Yonge, C. M. (Indian Forester, 1947)
Man's direct influence on marine life is of comparatively recent origin, for until about two hundred years ago the amount of fishing and whaling that was carried on was too small to upset the equilibrium of nature. With improved ships, apparatus, and technique, however, came a vast and indiscriminate slaughter of marine lie, and some species were exterminated altogether. There is now a general realization that wise cultivation of the sea is as necessary as wise cultivation of the land Professor Yonge gives a broad survey of the problem.